Pola Komunikasi Dan Interaksi Elit Desa dan Ex Kelompok Tani: Kontestasi dan Kolaborasi dalam Pengelolaan Koperasi Desa Merah Putih - Nursanty (STAI Bumi Silampari, 2026)
This research examines the patterns of communication and interaction between village elites and former farmer groups in the management of the Merah Putih Village Cooperative. The institutional transformation from farmer groups to village cooperatives has given rise to new dynamics in power relations and communication patterns at the village level. This qualitative research using a case study approach involved 25 informants consisting of village elites, former farmer group members, cooperative administrators, and community leaders. Data collection was conducted through in-depth interviews, participatory observation, and documentation studies over a period of six months. Data analysis used the interactive model of Miles and Huberman. The results of the study show that the communication patterns that have formed are patronage-based, with village elites dominating strategic decision-making. Contestation occurs in the areas of access to resources, distribution of economic benefits, and leadership legitimacy. However, collaboration is established through village deliberation mechanisms, compromise of interests, and division of roles within the cooperative's organizational structure. The findings indicate that although the dominance of the elite remains strong, there is room for negotiation that allows former members of farmer groups to participate in decision-making. This study contributes to the understanding of power dynamics in village cooperative governance and offers recommendations for strengthening inclusive participation in rural development.